Pitágoras y su teorema en 90 minutos - Strathern, Paul, 1940- (En 90 minutos., 2014)
An overview of the life and work of Pythagoras, arguably the first Western mathematician and philosopher, and the genius who established such concepts as abstract reasoning and deductive proof."The Big Idea" series aims for a clear-cut presentation of complex and revolutionary scientific ideas.